LITERATUR REVIEW: HOW TO MAINTENANCE VIP - Fatimah, Sarah; Sulistiadi, Wahyu (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2021)
In Marketing analysis, patient is an important stakeholder of the hospital. And VIP patients can be valuable to increased demand. Caring for very important persons (VIPs), including celebrities and royalty, presents medical, organizational, and administrative challenges, often referred to collectively as the “VIP syndrome. The situation often pressures the health care team to bend the rules by which they usually practice medicine. Caring for VIP patients requires innovative solutions so that their VIP status does not adversely affect the care they receive. Caring for very important persons (VIPs), including celebrities and royalty, presents medical, organizational, and administrative challenges, often referred to collectively as the “VIP syndrome”. Literature Review method from relevant database such as Google Scholar search engine until 2018. Total document selected by full text is 6 articles as literature review and total 12 article as references. Nine guiding principles in caring VIP patients is Don’t bend the rules, work as a team, communicate, Carefully manage communication with media, resist chairpersons syndrome, care should occur where it is most appropriate, protect the patients security, be careful about accepting or declining gifts and working with the patient's personal physicians. Particularly when dealing with a VIP, the hospital’s communications or public relations (PR) officer becomes an integral member of the rehabilitation team. Although staff members will always be tempted to treat VIPs in special ways, the temptation should be avoided. The needs and problems of our patients, not their status or influence, should drive our response to them in the ED. VIP patients need treat more respectfully, see them more quickly, and pay more attention to them.